The impact of group antenatal care on newborns: Results of a cluster randomized control trial in Eastern Region, Ghana - Veronica Apetorgbor; Elizabeth Awini; Bidisha Ghosh; Ruth Zielinski; Georgina Amankwah; Vida A. Kukula; Katherine James; John E.O. Williams; Jody R. Lori; Cheryl A. Moyer (BMC, 2024)
Abstract Background Maternal recognition of neonatal danger signs following birth is a strong predictor of care-seeking for newborn illness, which increases the odds of newborn survival. However, research suggests that maternal knowledge of newborn danger signs is low. Similarly, maternal knowledge of optimal newborn care practices has also been shown to be low. Since both issues are typically addressed during antenatal care, this study sought to determine whether group antenatal care (G-ANC) could lead to improvements in maternal recognition of danger signs and knowledge of healthy newborn practices, as well as boosting postnatal care utilization. Methods This cluster randomized controlled trial of G-ANC compared to routine individual antenatal care (I-ANC) was conducted at 14 health facilities in Ghana, West Africa, from July 2019 to July 2023. Facilities were randomized to intervention or control, and pregnant participants at each facility were recruited into groups and followed for the duration of their pregnancies. 1761 participants were recruited: 877 into G-ANC; 884 into I-ANC. Data collection occurred at enrollment (T0), 34 weeks' gestation to 3 weeks postdelivery (T1) and 6-12 weeks postpartum (T2). Comparisons were made across groups and over time using logistic regression adjusted for clustering. Results Overall, knowledge of newborn danger signs was significantly higher for women in G-ANC, both in aggregate (13-point scale) and for many of the individual items over time. Likewise, knowledge of what is needed to keep a newborn healthy was higher among women in G-ANC compared to I-ANC over time for the aggregate (7-point scale) and for many of the individual items. Women in G-ANC were less likely to report postnatal visits for themselves and their babies within 2 days of delivery than women in I-ANC, and there was no difference between groups regarding postnatal visits at one week or 6 weeks after birth. Conclusion This study illustrates that group ANC significantly improves knowledge of newborn danger signs and healthy newborn practices when compared to routine care, suggesting that the impact of G-ANC extends beyond impacts on maternal health. Further research elucidating care pathways for ill newborns and maternal behaviors around healthy newborn practices is warranted. Trial registration : ClinicalTrials.gov Identifier: NCT04033003, Registered: July 25, 2019 Protocol Available at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC9508671/ .